Static T2w MRU in Noncalcular Urinary Obstruction: Comparison of Its Two Techniques - Mohamed Abou El-Ghar; Ahmed Shokeir; Huda Rafaie; Tarek El-Diasty (The Scientific World Journal)
The purpose of this study was to compare the diagnostic accuracy of T2-weighted (T2w) MR urography (MRU) techniques — the standard MRU using fast spin echo (FSE) and postprocessing maximum intensity projection (MIP) and the single-shot MRU — in the diagnosis of ureteric obstruction in patients with noncalcular urinary obstruction. The study included 150 patients admitted to our center between January 2005 and December 2006. There were 203 renal units with noncalcular obstruction; 53 patients had bilateral obstruction. Patients with calcular obstruction were excluded. There were 85 males and 65 females with a mean age of 50 (range: 5–83) years. All patients were examined with static MRU using both single-shot (thick slab) and multisection MRU. Using single-shot MRU, we obtained images at the direct coronal and oblique coronal, as well as sagittal, planes for each renal unit. Postprocessing MIP for the standard coronal heavy T2 source images to obtain coronal and oblique images was done. Among the obstructed 203 units, the intrinsic causes were present in 157 units (151 were stricture and six were ureteric tumors), while the extrinsic causes were present in 46 units (35 bladder tumor, four ureterocele, five retroperitoneal fibrosis, one prostatic tumor, and one local pelvic recurrence after radical cystectomy for bladder cancer). The overall accuracy of single-shot MRU was 89% and was 93% for the multisection MRU in cases of intrinsic ureteric obstruction, while in cases of extrinsic obstruction, it was 20% for single-shot MRU and 96% for multisection MRU. T2w static MRU is a very useful technique in diagnosing noncalcular ureteric obstruction. Multisection MRU has a high diagnostic accuracy and reliability over that of the single-shot technique. The single-section technique is very rapid and useful in diagnosing ureteric stricture so it could be used as a localizer, while multisection images with postprocessing MIP is mandatory, especially in cases of suspected ureteric tumors or extraureteric causes.